National reign of the elderly: engine of potential for tourism in Tibasosa – Boyacá (Revista cientifica In Vestigium Ire, 2019)
Festivities are reference instruments for different cultural acts or events in which the human being is immersed. Colombia is a clear example, since its cultures are framed in the different events that are carried out during a year, one of them is the Reign of the Third Age in Tibasosa, Boyacá- Colombia has been catalogued as the second country with more festivities in the world, according to the annual survey carried out by Gallup, WIN and the Consultancy Center. In this sense, a documentary, descriptive and mixed type of research was carried out, which allowed the analysis of the state of the National Kingdom of the Third Age in the municipality of Tibasosa, where it was concluded that there is a scarce cultural diffusion, and thus overall, it was investigated on the influence that this event has on the generation of increases in the tourist sector at a municipal, departmental and national level, paying attention to diverse strategies to this and other festivities that would lead to the potential of tourism as a development engine in all its dimensions. In effect, it was considered important to take as references, informative, theoretical portals with patrimonial foundations and programs and projects of the government, in order to establish the importance of the events and the commitment, participation and action of a part of the society that, in many moments has been forgotten.
Keywords: Heritage; kingdom; tourism